Engineering Fully Organic and Biodegradable Superhydrophobic Materials. Issue 1 (8th October 2018) - Milionis, Athanasios; Sharma, Chander Shekhar; Hopf, Raoul; Uggowitzer, Michael; Bayer, Ilker S.; Poulikakos, Dimos
Abstract: The development of fully organic (cellulose/wax based), biodegradable, and hierarchically textured superhydrophobic material, inspired by natural, self‐cleaning plants, like the Lotus leaf is reported. The developed material can reproduce in a controllable and artificial manner the chemical composition and material properties of these natural surfaces. At the same time, the fabrication protocol described here enables realization of properties beyond the ones found in the natural leaves, by allowing facile tuning of the topographical and mechanical properties. The surface topography consists of a micropillar structure assembly with, to the best of the authors' knowledge, the highest to date reported aspect ratio (7.6) for cellulose materials. Additionally, control and tunability of the material's mechanical properties are also demonstrated, which is rendered softer (down to 227 MPa Young's modulus from 997 MPa base value) by adding glycerol as a natural plasticizer. Finally, the self‐cleaning properties are demonstrated and the biodegradability of the material is evaluated in a period of ≈3 months, which confirms full biodegradation. Additionally, water drop and jet impact, and folding tests demonstrate that the material can reasonably sustain its wettability properties. Such a truly bioinspired and biodegradable material system could find potential use in various bioengineering applications. Abstract : A fully organic and biodegradable material with self‐cleaning behavior is developed, inspired by the common chemical composition found in plants. The main constituents are micropatterned cellulose substrates and wax sub‐micrometer rough coatings. Capabilities for microstructuring high aspect ratio (7.6) cellulose microarrays are demonstrated while the mechanical properties can also be tuned with the addition of natural plasticizers.